2018
DOI: 10.1177/1534508418775805
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Validity of Kindergarten Progress Monitoring Measures Across the School Year: Application of Dominance Analysis

Abstract: Although several measures are available for monitoring kindergarten reading progress, little research has directly compared them to determine which are superior in predicting year-end reading skills relative to other measures, and how validity may change across the school year as reading skills develop. A sample of 426 kindergarten students who were considered to be at risk for reading difficulty at the start of kindergarten were monitored across the year with a set of paper-based progress monitoring measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(62 reference statements)
1
8
0
1
Order By: Relevance
“…If a child read all 50 words in under a minute, their score was prorated. Previous WIF research with children in U.S. kindergarten showed word reading skills at mid year (Clemens et al, 2019) and growth in word reading in the latter half of the year (Clemens et al, 2018) predicted year-end reading skills.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…If a child read all 50 words in under a minute, their score was prorated. Previous WIF research with children in U.S. kindergarten showed word reading skills at mid year (Clemens et al, 2019) and growth in word reading in the latter half of the year (Clemens et al, 2018) predicted year-end reading skills.…”
Section: Methodsmentioning
confidence: 96%
“…This growth was the fastest between Reception Terms 2 and 3 (winter to spring), with word reading predicted by, and reciprocally related to, phonemic awareness and grapheme–phoneme knowledge (Clayton et al, 2020). Moreover, research with U.S. children has indicated that word reading growth in the second half of their kindergarten year is predictive of literacy skills at year end (Clemens et al, 2018, 2019). To date, however, research examining word reading acquisition in very nascent readers is just beginning to emerge (T.…”
Section: Developing Code-related Skills In Beginning Reading Instructionmentioning
confidence: 99%
“…Path analysis assumptions were checked; all parameters were continuous and normally distributed. Multicollinearity between NZWIF-Y1 mLCS and LSF mLCS ( r = .85) would result in the dominant variable subsuming effects of the other (Barbeau et al, 2019; Clemens et al, 2019). Therefore, separate path analysis models were undertaken modeling contributions of (a) onset phoneme awareness (FSF mLCS ) and letter-sound correspondence (LSF mLCS ) with school-entry skills and (b) onset phoneme awareness (FSF mLCS ) and word reading (NZWIF-Y1 mLCS ) with school-entry skills.…”
Section: Methodsmentioning
confidence: 99%
“…Dominance analysis involves testing all possible combinations of predictors in separate regression models (i.e., subset models) to reveal the additional contribution of each predictor relative to other predictors under study. Dominance analysis has been used in several studies to identify the skills or measures that are most important in predicting reading skills on a concurrent or longitudinal basis (e.g., Clemens et al, 2019; Fuchs et al, 2004; Mellard et al, 2012; Schatschneider et al, 2004; Tighe & Schatschneider, 2014). However, dominance analysis has not been used to investigate the extent to which component reading skills and knowledge sources differentially predict performance across different tests of reading comprehension.…”
Section: Dominance Analysismentioning
confidence: 99%